A Literature Review on Risk and Protection Factors of Burnout in Healthcare Students: Kajian Literatur: Faktor-Faktor Risiko dan Proteksi Burnout pada Mahasiswa di Bidang Kesehatan - Kusumawardani, Anggraeni; Hidayat, Dede Rahmat (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
The pandemic was a test of the boundaries and challenges to conventional practices in healthcare education systems. During the emergent pandemic situation, several critical decisions were promptly taken, disregarding students' consent. For instance, healthcare students were encouraged to serve as health volunteers. The surge in responsibilities led to an increase in burnout cases among students, a decline in motivation, academic achievement, and an inclination to consider dropping out or discontinuing education. This study aimed to investigate risk and protection factors contributing to burnout in healthcare students, categorizing the elements into intrinsic and extrinsic. The method employed a literature review following the PRISMA guidelines. Four databases, namely ProQuest, PubMed, Google Scholar, and DOAJ were searched in March 2022, leading to 18 articles meeting the criteria out of 3,835 initially identified. The results showed at least thirty factors contributing to burnout risk and protection, with two-thirds falling into intrinsic and the rest in the extrinsic group. The findings suggested that burnout in healthcare students primarily stems from internal factors rather than environmental influences. These results enhance the design of interventions to prevent and address student’s burnout more effectively and efficiently.